2021
DOI: 10.1016/j.ijid.2020.11.140
|View full text |Cite
|
Sign up to set email alerts
|

Novel stepwise approach to assess representativeness of a large multicenter observational cohort of tuberculosis patients: The example of RePORT Brazil

Abstract: RePORT-Brazil. Illicit drug use, the presence of diabetes, and history of prior TB were associated with unfavorable TB treatment outcomes; illicit drug use was associated with such outcomes in both cohorts. Conclusions: There were important similarities in demographic characteristics and determinants of clinical outcomes between the RePORT-Brazil cohort and the Brazilian National registry of TB cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 14 publications
(16 reference statements)
2
41
0
Order By: Relevance
“…RePORT-Brazil includes five study sites, located in cities with high TB burden: Salvador, Manaus, and Rio de Janeiro [20]. One main objective of the consortium is to describe the clinical outcomes of TB treatment and latent Mtb infection in Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RePORT-Brazil includes five study sites, located in cities with high TB burden: Salvador, Manaus, and Rio de Janeiro [20]. One main objective of the consortium is to describe the clinical outcomes of TB treatment and latent Mtb infection in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…SINAN is the Brazilian National System of Notification of Diseases [23], and includes diseases that require notification in all states and municipalities of Brazil; TB is a notifiable disease. The details of SINAN have been previously described [20]. PWTB reported to SINAN are diagnosed following the criteria in the Brazilian Manual of Recommendations for Tuberculosis control [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we included data from close TB contacts identified in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil [12] between TPT was recommended according to the National TB Control Program of Brazil [2,11]. TPT was also initiated based on the physician's decision to treat and RePORT-Brazil did not influence such decision.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we included data from close TB contacts identified in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil [12] between August 27 th , 2015, and July 18 th , 2019, with follow-up between 6 and 24 months. The RePORT-Brazil consortium is an ongoing, multicenter, cohort study, which follows culture-confirmed pulmonary TB cases and their close contacts.…”
Section: Methodsmentioning
confidence: 99%